Eksistensi Isbat Nikah Setelah Berlakunya Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 Ditinjau dari Kepentingan Anak - Pratama, Indra; Hamid, Arfin; Ratnawati, Ratnawati (Universitas Negeri Malang, 2024)
This study aims to analyze the urgency of the status of illegitimate children in the perspective of Islamic law and the existence of isbat nikah after the enactment of the Constitutional Court Decision Number 46/PUU-VIII/2010. This study uses a normative research method that focuses on legal norms. The data collection technique uses a literature study by reviewing relevant legal materials. Data are analyzed qualitatively through the creation of abstractions, namely a summary of the core, process, and data statements. The results of the study indicate that children born out of wedlock in Islamic law only have a bloodline and inheritance relationship with their mother. Fatwa of the Indonesian Ulema Council Number 11 of 2012 only aims to provide legal protection for illegitimate children, but does not legally recognize the child's bloodline relationship with their biological father. Marriages that are not yet legally valid must submit an application for isbat nikah, but after the enactment of the Constitutional Court Decision Number 46/PUU-VIII/2010 illegitimate children can have civil relations without an official marriage but are proven by genetic testing.